Empowering women in Lunjuk Village through the creation of MSMEs ginger products - Guswarni Anwar; Hendri Bustamam; Kasrina Kasrina; Hefri Oktoyoki; Gunggung Senoaji (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Since 2011, the Forum Petani Bersatu (FPB) Women's Group in Lunjuk Village has been embroiled in tenurial conflict, resulting in the loss of their plantation land. Currently, most members work as laborers in oil palm plantations, earning a limited income. This community empowerment program aims to empower them as the mainstay of their family's economy by establishing a family micro-enterprise that produces processed ginger products.Â  This is due to the easy and affordable availability of ginger in their vicinity. At the start of the activity, a counseling method was used to emphasize the importance of entrepreneurship.Â  Following this, participants received training on ginger processing, including the production of ginger flour for instant ginger drinks, candy, dodol, and ginger syrup. The outcome of the activity was the establishment of SMEs that produce processed ginger products with an official P-IRT license from the Seluma Health Office. The small and medium-sized enterprise (SME) has been registered with the Seluma Regency Industry, Trade, and Cooperative Office to obtain a business license (HO) and receive assistance from the office. Currently, the SME produces ginger flour and markets it not only in Lunjuk village but also in Bengkulu City.